Polycyclic aromatic hydrocarbon (PAH) variability in the lower Tar River N.C. from a legacy hazardous waste site as a function of hydrological conditions - Reed, Daniel J (East Carolina University, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are a class of trace organic contaminants that can enter the environment from both natural and anthropogenic sources. Of these compounds, 16 are listed as high-priority contaminants by the EPA. PAHs are either petrogenic or pyrogenic. One potential anthropogenic source of PAHs is fuel seeps. The Tar River has been and is currently being affected by a legacy fuel seep from underground storage tanks in the area that have undergone remediation. Although research has been done on PAHs in fuel seeps and on PAH remediation, that research addressed sites soon after remediation. Research has generally not addressed how PAH contamination from a legacy seep historically remediated. This research aims to determine how a legacy seep affects PAH contamination in the Tar River as a function of river flow. To determine how the legacy seep is affecting the Tar River at different flow conditions, sites at and around the potential contamination site, Town Creek, were sampled over several months in 2022 and 2023. These samples were then filtered to separate particulates and dissolved PAHs. The identity and concentration of PAHs were determined using a gas chromatograph- mass spectrometer. The total PAHs and ratio of parent PAHs to the total PAHs were found to have no correlation with the gauge height of the river or the dissolved organic carbon (DOC) of the sites sampled. This suggests that the PAH contamination in the Tar River was not driven by river flow. Parent-to-total PAH ratio of less than 0.5 in the dissolved phase at the upstream (TC1) sampling site during 10-2-22 and 11-20-22 sampling events, and at a downstream site (D1) during a 11-20-22 sampling event, suggest that a petrogenic source affected these sites during these events. Individual PAH distributions at D1 had a petrogenic signature during a low flow period in the Tar River suggesting that it may have been affected by Town Creek during low flow events. This research adds to the knowledge base of contamination sites that have undergone remediation in the past and how they may still affect their environments.
Keywords: PAH; GC-MS; Legacy Contamination; Polycyclic aromatic hydrocarbons--North Carolina; Tar River (Person County-Beaufort County, N.C.); Biofilms--North Carolina; Hazardous waste sites--Environmental aspects--North Carolina